Experimental and CFD study of a new design of a direct-flow cyclone - E. V. Flisyuk; V. S. Toptalov; O. M. Flisyuk; I. G. Likhachev; Yu. M. Kotsur (Разработка и регистрация лекарственных средств)
Introduction. Purification of gas streams plays an important role in many industries in the field of environmental engineering. When implementing such measures, cyclones are often used – devices for cleaning gas streams from fine particles. In the pharmaceutical industry solving such problems requires the use of compact, highly efficient devices, for the development and study of which CFD-modelling methods have recently been increasingly used. The paper presents a comparison of the results of CFD-modelling of the gas purification process in a direct-flow cyclone of a new design and the capture efficiency in this apparatus obtained as a result of experimental studies.Aim. Comparison of the results of numerical modelling of the gas purification process in two configurations of a direct-flow cyclone of a new design with the experimental results.Materials and methods. The FlowVision software package was used for numerical CFD-modelling of the separation process in the studied device. The motion of the discrete phase – particles – was described using the Lagrangian particle model. Rosin-Rummler distribution with a minimum diameter of 15 microns, a median of 40 microns, and a maximum of 120 microns was used to distribute the particles by size. The experiments were carried out on an experimental setup, the main part of which was a direct-flow cyclone, a centrifugal fan and a screw doser. Technical talc was used as a model material, the dispersed particle distribution of which was determined by laser diffraction on a SALD-2300 particle analyzer (Shimadzu, Japan).Results and discussion. The CFD-model of the device allowed us to determine the gas velocity field, flow trajectories and particle capture efficiency in the studied configurations of a direct-flow cyclone. Based on the information about the gas velocity field and flow trajectories, conclusions were made about the most effective 4 design solutions. Comparison of the numerical simulation results and the experimental results showed good convergence.Conclusion. The developed design of the direct-flow cyclone showed good efficiency of fine particle capture. Numerical CFD-modelling allowed us to determine design features that negatively affect the efficiency and to optimize the design of the device. Good convergence of the model and experimental results confirms the possibility of using CFD-programmes for accurate modelling of technological processes and determining their parameters.